2013
DOI: 10.1109/access.2013.2267611
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Domain Analytics Applied to PV Module Lifetime and Degradation Science

Abstract: A better understanding of the degradation modes and rates for photovoltaic (PV) modules is necessary to optimize and extend the lifetime of these modules. Lifetime and degradation science (L&DS) is used to understand degradation modes, mechanisms and rates of materials, components and systems to predict lifetime of PV modules. A PV module lifetime and degradation science (PVM L&DS) model is an essential component to predict lifetime and mitigate degradation of PV modules using reproducible open data science. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 47 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…5. The statistical pathway model generated using Principle 1 for the variables T ime, Hac, IR2, IRBS1, and P max was found to contain the most information content and mapped well to domain knowledge [26].…”
Section: Landds Analytics: Discussion a Uv Testing Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…5. The statistical pathway model generated using Principle 1 for the variables T ime, Hac, IR2, IRBS1, and P max was found to contain the most information content and mapped well to domain knowledge [26].…”
Section: Landds Analytics: Discussion a Uv Testing Responsesmentioning
confidence: 99%
“…Of the 32 possible combinations of the chosen variables that were modeled with each of the two previously described principles of variable selection, the Principle 1 modeling technique applied to the variables T ime, Hac, IR2, IRBS1, and P max was found to possess the most information content and mapped well to domain knowledge [26]. A full prognostic model was not developed due to some limitations in the data set, though valuable observations about PV module response to damp heat testing conditions were evident from the statistical analysis.…”
Section: Statistical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first principle examines only univariate relationships based on a selection of known functional forms directly from one variable to another, and performs iterative variable selection steps on the basis of a 0.2 cutoff of adjusted-r-squared value. The second principle examines the collective additive influence of variables upon one another utilizing Akaike Information Criterion (AIC) values to perform stepwise variable selections iteratively to indicate networks of relationships between the variables [27].…”
Section: B Statistical Modelingmentioning
confidence: 99%
“…Considerable research has already been published on observed degradation modes or mechanisms, but it is not clear how these mechanisms interact or how the network of mechanistic degradation pathways, acting in parallel or series, actually produce the degradation in performance. 39 Reliability research efforts conducted on complete modules are typically conducted in the laboratory under accelerated aging conditions, exposing the module to high doses of heat/ humidity and/or light well in excess of the extremes of the real world. Relative humidity of 85 C and 85% is a typical exposure condition for accelerated aging.…”
Section: Mesoscale Description Of Solar Cell Interfaces and Contactsmentioning
confidence: 99%